Factors Affecting Methane Adsorption and Storage in Black Shales of Varying Maturity and Kerogen Type - Haq, I.U. (Unconventional Resources Technology Conference (URTEC), 2021)
Shale gas as energy resource play a significant role in the energy interdependence of any region and further research is needed to overcome the challenges by evaluating the factors that affects the methane storage capacity in shale reservoirs. This research evaluates the methane storage capacity of a potential unconventional reservoir, Semantan Formation, in the Peninsular Malaysia as well as factors responsible for the variation in the gas storage on the basis of mineralogy, maturity, and kerogen type by measuring methane adsorption isotherms on black shales from Semantan Formation as well as Oatka Creek Formation, Appalachian Basin, USA. X-ray Diffraction analysis were carried out to characterize the mineralogy of shales from both the Formations. TOC analysis and Rock-eval pyrolysis were utilized to determine the organic richness, maturity, and kerogen type, whereas pore structure and pore types were analyzed using Field-Emission Scanning Electron Microscopy. Black shales from both the Formations have shown a considerable storage potential due to the presence macro and meso-pores associated with mineral matter in the matrix. Increasing the pressure gradually from 1 MPa to 13 MPa, at a constant temperature, has shown a significant increase in the sorption capacity of shales from both the Formations. Results shows that organic richness and kerogen type has a significant impact on the methane sorption capacity of shales. The black shales hosting type-III kerogen provided more sites for gas adsorption than shale hosting type-II kerogen. The organic richness i.e., TOC > 5 of the shale hosting type-III kerogen has shown higher methane adsorption compared to shale of low TOC type-III kerogen. Microscopic analysis revealed that the pore structure and mineral matter is similar in both the shales where the dominant inter-mineral pores are hosted by clay minerals, however, pores abundance vary in both shales due to visible mechanical compaction effects in Semantan shales. Black shales of Semantan Formation holding type-III kerogen has shown considerable gas sorption capacity and can act as a potential gas shale resource in Peninsular Malaysia. Â© 2021 Unconventional Resources Technology Conference (URTeC)